Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kemiskinan dengan Belanja Daerah Sebagai Variabel Intervening di Kabupaten Malang - Muhammad Averroes Al- Khawarizmi; Marseto Marseto; Sishadiyati Sishadiyati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
Malang regency has the highest poverty rate in East Java followed by Jember Regency. Regional financial management by the local government as a power holder is something that can affect how the level of poverty and welfare of the people in the area. This study aims to find out how the influence of Regional Native Income (PAD) and Balance Fund (DAPER) on Poverty directly and indirectly through Regional Expenditure (BD) in Malang Regency. The type of data used in this study is secondary data, time series with a period of time from 2009 to 2020 and processed using multiple regression analysis methods for path analysis testing. The results of this study showed that the region's native income has a significant negative influence on poverty, the balance fund has a significant negative impact on poverty, the local native income has a significant negative influence through regional spending on poverty, and the balance fund has a significant negative contribution through regional spending on poverty.